BRE12-158: A Postneoadjuvant, Randomized Phase II Trial of Personalized Therapy Versus Treatment of Physician's Choice for Patients With Residual Triple-Negative Breast Cancer. Issue 4 (1st February 2022) - Schneider, Bryan P.; Jiang, Guanglong; Ballinger, Tarah J.; Shen, Fei; Chitambar, Christopher; Nanda, Rita; Falkson, Carla; Lynce, Filipa C.; Gallagher, Christopher; Isaacs, Claudine; Blaya, Marcelo; Paplomata, Elisavet; et al.
Abstract : PURPOSE: Patients with triple-negative breast cancer (TNBC) with residual disease after neoadjuvant chemotherapy (NAC) have high risk of recurrence with prior data suggesting improved outcomes with capecitabine. Targeted agents have demonstrated activity across multiple cancer types. BRE12-158 was a phase II, multicenter trial that randomly allocated patients with TNBC with residual disease after NAC to genomically directed therapy versus treatment of physician choice (TPC). PATIENTS AND METHODS: From March 2014 to December 2018, 193 patients were enrolled. Residual tumors were sequenced using a next-generation sequencing test. A molecular tumor board adjudicated all results. Patients were randomly allocated to four cycles of genomically directed therapy (arm A) versus TPC (arm B). Patients without a target were assigned to arm B. Primary end point was 2-year disease-free survival (DFS) among randomly assigned patients. Secondary/exploratory end points included distant disease-free survival, overall survival, toxicity assessment, time-based evolution of therapy, and drug-specific outcomes. RESULTS: One hundred ninety-three patients were randomly allocated or were assigned to arm B. The estimated 2-year DFS for the randomized population only was 56.6% (95% CI, 0.45 to 0.70) for arm A versus 62.4% (95% CI, 0.52 to 0.75) for arm B. No difference was seen in DFS, distant disease-free survival, or overall survival for the entire or randomized populations. There was increased uptake of capecitabine for TPC over time. Patients randomly allocated later had less distant recurrences. Circulating tumor DNA status remained a significant predictor of outcome with some patients demonstrating clearance with postneoadjuvant therapy. CONCLUSION: Genomically directed therapy was not superior to TPC for patients with residual TNBC after NAC. Capecitabine should remain the standard of care; however, the activity of other agents in this setting provides rationale for testing optimal combinations to improve outcomes. Circulating tumor DNA should be considered a standard covariate for trials in this setting.